Optimizing firefighting resilience in airports through genetic algorithms and decision-making frameworks - Yulong Zhu; Wei Tian; Xuhong Jia; Quanyi Liu (Journal of Safety Science and Resilience)
Aviation transport infrastructure is key to international commerce and cultural exchange, with any emergency potentially causing major impacts on contemporary society. With advancements in technology and growing societal needs, modern airports are evolving toward smarter and more integrated systems. While transportation engineers and planners aim to bolster resilience in subsystems and transport management with new technologies and diverse strategies for effective risk management, the growing complexity of disaster-inducing factors and fire dynamics in airport systems somewhat diminishes the accuracy of existing risk vulnerability analyses. It drives the demand for enhanced firefighting resilience. This study discusses assessment and improvement strategies for enhancing the resilience of airport firefighting systems in the context of smart airports. Specifically, we analyze the resilience characteristics of airport firefighting systems, which can be subdivided into four dimensions: stability capability, resistance capability, recovery capability, and adaptability capability. Furthermore, by integrating human, mechanical, environmental, and managerial elements, a comprehensive resilience evaluation indicator system is constructed. We propose a modified composite weight calculation framework that innovatively introduces genetic algorithm (GA) in the weight combination process to simplify the model into a constrained minimization problem from a mathematical perspective, thus making the ranking results reflect ordinal and intensity information. The findings highlight the significance of technological advancements, emergency response capabilities, expertise in fire management, cross-departmental collaborative responses, personnel psychological quality, and accident investigation skills in enhancing the resilience of airport firefighting systems. Although the comprehensive evaluation model based on expert knowledge still focuses primarily on resistance, the criterion of adaptation capability has a more pronounced increasing trend in weight under correction, highlighting its significant role and potential in future airport firefighting resilience indicators. This research aims to offer guidance to the aviation sector and managers for devising appropriate protection strategies, thereby improving public safety at airports.